The Effect of Changing Position and Early Ambulation after Cardiac Diagnostic Catheterization on Back pain and Bleeding - M Sabzaligol; E Shariat; Sh Varaei; A Mehran; Sh Bassampour (Tehran University of Medical Sciences, 2010)
Background & Aim: The prevalence of cardiovascular diseases is high in most of the countries. Cardiac catheterization is a routine diagnostic test for coronary heart diseases. In order to minimize the post-procedure complications, patients are restricted to bed for 8-24 hours in flat position. The aim of this study was to assess the effect of changing position and early ambulation on back pain and the amount of bleeding after cardiac catheterization. Methods & Materials: In this quasi-experimental study, 90 patients undergoing diagnostic angiography were selected using convenience sampling method in Shariati hospital. The patients were allocated in two intervention and control groups. The control group remained in supine position for 8-24 hours and the sandbag remained for eight hours. The patients;apos position in the intervention group was intermittently changed during the first hour after catheterization. The head of bed was set at 15 degree angle. In the second hour, the position changed to flat and the head of bed raised to 30 degree. In the third hour, the head of bed angle was set in 45 degree. In the first three hours sandbag was placed in catheter insertion site. After the third hour, patients could rest in any position (15-30 degree). Patients were ambulated in the sixth hour. Back pain intensity and level of bleeding were assessed immediately after admission, in the sixth, 24th hour and after the seventh day of catheterization. Results: The results indicated that there was no statistically significant difference in age, gender, education level, back pain intensity, and the level of bleeding immediately after the catheterization. Back pain intensity was lower in the intervention group than the control one after 6 and 24 hours of catheterization (P<0.001). There was no statistically significant difference between the intervention and control groups in the level of bleeding after 6 hours, 24 hours, and seven days of catheterization (P>0.05).Conclusion: Patients should be allowed to change their positions in bed cardiac catheterization. Patients can be ambulated earlier (in the sixth hour) after cardiac diagnostic catheterization.